ANALYSIS OF THE EFFECT OF STRESS MANAGEMENT ON WORK PRODUCTIVITY - R. Taufiq Nur Muftiyanto (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
This literature research aims to analyze the effect of stress management on work productivity through a systematic investigation of various existing literature, studies and research. Drawing on theories of human resource management, occupational health, as well as principles of organizational psychology, this study explores how stress impacts individuals in the workplace and how effective stress management practices can be an important tool for improving job performance and satisfaction. Using literature investigation methods, this study collects and analyzes data from various previous research sources including journal articles, books and research databases. The results of the analysis show that work stress has a negative impact on individual work productivity, causing decreased performance, low job satisfaction, and mental and physical health problems. On the other hand, implementing stress management such as relaxation techniques, mindfulness training, social support, and improving communication has proven effective in reducing stress levels. Furthermore, the study found that policies and programs designed to manage workplace stress not only increase work productivity but also bring additional benefits such as increased employee loyalty, job satisfaction, and overall employee well-being. This research provides valuable insights for corporate leaders, human resources practitioners, and policy makers about the importance of effective stress management strategies to increase work productivity. The implications of these findings suggest that investing in stress management programs is a profitable investment for improving operational efficiency and strengthening overall organizational health